Simplicity Character Value Development in Gedongkuning State Elementary School - Lili Nur Amaliyah; Subiyantoro (EDUKASI : Jurnal Pendidikan Islam (e-Journal), 2022)
Character building guides students to become human beings with character, and simplistic values ​​are a person's habit of behaving according to their needs and abilities. This study aims to determine how students' character development is based on the value of simplicity in SDN Gedongkuning. The research was conducted in field research with exploratory qualitative research. The data collection technique in this study interviewed several informants: the school principal, our students and teachers. Data analysis techniques in this study used the theory of Miles and Huberman's data reduction, data presentation and conclusions. The results of this study can be concluded that SDN Gedongkuning applies the character value of simplicity, including 1) Getting used to students helping friends who are in trouble; 2) Assign students to dress modestly and avoid using items such as shoes, bags or jewellery that are too expensive; 3) Encouraging students to bring pocket money reasonably. By applying the value of simplicity so that there are no gaps between students and others.